Risk Factors and Outcomes for the Development of Malignancy in Lung and Heart-Lung Transplant Recipients - Michael J Metcalfe; Demetrios J Kutsogiannis; Kathy Jackson; Antigone Oreopoulous; John Mullen; Denis Modry; Justin Weinkauf; Dale C Lien; Ken C Stewart (Canadian Respiratory Journal)
BACKGROUND: Many factors may limit survival from lung and heart-lung transplantation, including malignancy.